Preliminary Assessment of Sea Star (Echinodermata, Asteroidea) Diversity in the Coastal Magellanic Region (South Chile) and Their Geographical Distribution - Vantomme, Luka; Jossart, Quentin; Gerard, Karin Francoise; Danis, Bruno; Moreau, Camille (My University, 2023)
Sea stars are a diverse and important component of the Southern Ocean benthos. However, scarce information is available regarding their diversity, distribution, evolution, and taxonomic uncertainties persist for multiple taxa. The Magellanic Region (south of Chile) remains under-sampled despite its pivotal location for species distribution and diversity, being located at the crossroad of three ocean basins. In this study, we assessed the biodiversity of coastal Magellanic sea stars and their affinities with other oceanic bioregions. An integrative approach combining morphological identification with DNA barcoding was implemented to highlight taxonomic discrepancies such as suspected synonymy and unrecognised diversity. Firstly, we identified a total of 15 species from the coastal Magellanic Region and reported the occurrence of Cycethra frigida Koehler, 1917 for the first time in this region. The distribution of these 15 species ranged from only in South America to circumpolar, bipolar, or possibly cosmopolitan. Secondly, we highlighted possible synonymy in two species pairs within the genera Anasterias and Odontaster. This preliminary biodiversity assessment forms an important baseline for monitoring and conservation purposes, especially in the face of distribution shifts as a response to climate change and the increased presence of invasive species. Developmental mode has previously been suggested to be important in shaping biogeographical patterns. However, developmental mode was insufficient to explain the observed patterns, and other factors (e.g., physiological constraints, competition, bathymetrical range, and the possibility of passively rafting on kelp) are suggested to be at least equally important. Finally, an increase in barcoding effort is needed to better capture phylogeographic patterns for each species, both by increasing the number of specimens investigated and by covering a broader geographical range.
Keywords: southern ocean; sub-antarctic; dna barcoding; ntegrative taxonomy; starfish